(untitled) (Nativa, 2024)
ABSTRACT: The performance of the total value chain is a sustainability study. Therefore, it is necessary to control performance to ensure the competitiveness of the coffee agro-industry in Kalibaru; the actual conditions produced have yet to show the achievement of minimum standards. This research identified process performance activities in each dimension by farmers, traders, and the coffee industry. Data was collected by cluster random sampling involving nine farmers, three traders, two industries, and three experts; in contrast, the data collection technique was carried out in 3 stages: desk study, focus group discussions, and in-depth interviews. The method used is the Supply Chain Operations Reference (SCOR), and the aggregation method determines the dimension values ​​for each metric. The results showed that the measurement of the total farmer value chain with the dimensions of reliability (63.62%), agility (62.66%), and asset management (63.91%) was in the medium category for traders who were included in the medium category, namely power responsiveness (66.94%), agility (65.00%), cost (64.10%) and for industry only the cost dimension (62.16%) is included in the medium category, while the other dimensions are in the value category above 70.00%. Keywords: value chain; total performance; agroindustry coffee. Desempenho da cadeia de fornecimento para a agroindústria de café em Kalibaru, Indonésia RESUMO: O desempenho de toda a cadeia de valor é um estudo de sustentabilidade, portanto, é necessário controlar o desempenho para a competitividade da agroindústria cafeeira em Kalibaru, as reais condições produzidas ainda não demonstraram o alcance dos padrões mínimos. Esta pesquisa identificou atividades de desempenho de processos em cada dimensão por parte de agricultores, comerciantes e da indústria cafeeira. Os dados foram coletados por amostragem aleatória por conglomerados envolvendo nove agricultores, três comerciantes, duas indústrias e três especialistas. Em contrapartida, a técnica de recolha de dados foi realizada em 3 fases: estudo documental, discussões em grupos focais e entrevistas em profundidade. O método utilizado é o Supply Chain Operations Reference (SCOR), e o método de agregação determina os valores das dimensões para cada métrica. Os resultados mostraram que a medição da cadeia de valor total do agricultor com as dimensões de confiabilidade (63,62%), agilidade (62,66%) e gestão de ativos (63,91%) estavam na categoria média para os comerciantes incluídos na categoria média, nomeadamente energia capacidade de resposta (66,94%), agilidade (65,00%), custo (64,10%) e para a indústria apenas a dimensão custo (62,16%) está incluída na média da categoria, enquanto as demais dimensões estão na categoria de valor acima de 70,00%. Palavras-chave: cadeia de valor; desempenho total; agronegócio cafeeiro.